Engendering democratic transition from conflict : women's inclusion in Northern Ireland's peace process - Racioppi, Linda; O'Sullivan See, Katherine (2006)
Contiene bibliografía
Keywords: Mujer; Paz; Terrorismo; Irlanda del Norte